2016
DOI: 10.1590/1981-6723.7915
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição de fibra de aveia sobre as propriedades físico-químicas de hambúrguer cozido e congelado com redução de gordura e sal

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Efeito da adição de fibra de aveia sobre as propriedades físico-químicas dehambúrguer cozido e congelado com redução de gordura e sal Effect of the addition of oat fiber on the physicochemical properties of cooked frozen hamburger with reduced fat and salt ResumoNovos produtos cár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 29 publications
2
14
0
12
Order By: Relevance
“…The chia seeds addition did not alter (P>0.05) both L * , b * and C * , but grilling process increased (P<0.05) CIE L * and CIE b * values. A similar result was also reported by TREVISAN et al, (2016) who observed that CIE b * values have increased in grilled chicken burgers when oat fiber was added.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The chia seeds addition did not alter (P>0.05) both L * , b * and C * , but grilling process increased (P<0.05) CIE L * and CIE b * values. A similar result was also reported by TREVISAN et al, (2016) who observed that CIE b * values have increased in grilled chicken burgers when oat fiber was added.…”
Section: Resultssupporting
confidence: 88%
“…They also supposed that varied results could be due to that obtained on textural properties of meat products depending on amount and type of fiber added. This approach can be confirmed with the study of TREVISAN et al, (2016), who observed that both the hamburgers with 3% and 6% of added oat fiber showed values for hardness, cohesiveness and chewiness similar to those of the control. Table 3 shows the color characteristics of raw and grilled chicken burgers prepared with different levels of chia seeds.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Traditional meat products have a high fat content, and from the nutritional point of view, a reduction in fat content aims to help consumers reduce the intake of large amounts of saturated fatty acids and cholesterol from animal fat. This excessive consumption is associated with the possible development of cardiovascular disease and other types of chronic diseases (Del Nobile et al, 2009;Trevisan et al, 2016). On Brazil, according to data from the Health Ministry, obesity has increased by 60% in the last ten years, contributing to high rates of chronic diseases like diabetes and hypertension (Brazil, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During the manufacture of meat products, some ingredients are used to provide variety and improve cooking properties (Trevisan et al, 2016;Telis & Nicoleti, 2009;Tekin et al, 2010) and sensory characteristics, increase stability and reduce production costs (Akwetey & Knipe, 2012;López-Vargas et al, 2014;Ramadhan et al, 2011). The heat treatment during product preparation provides physical, chemical and structural changes to its components by the effect of heat (Borba et al, 2013) and can change the quality and yield due to the composition of product.…”
Section: Introductionmentioning
confidence: 99%